2021
DOI: 10.1002/ptr.7271
|View full text |Cite
|
Sign up to set email alerts
|

Peonidin‐3‐O‐glucoside and cyanidin increase osteoblast differentiation and reduce RANKL‐induced bone resorption in transgenic medaka

Abstract: Experimental and clinical studies suggest a positive impact of anthocyanins on bone health; however, the mechanisms of anthocyanins altering the differentiation and function of osteoblasts and osteoclasts are not fully understood. This work demonstrates that dietary anthocyanins and resveratrol increased proliferation of cultured human hFOB 1.19 osteoblasts. In addition, treatment of serum starvation of hFOB osteoblasts with anthocyanins and resveratrol at 1.0 μg/ml reduced apoptosis, the Bax/Bcl-2 ratio, p53,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…It has been proven that bone metabolism can be modulated by nutrients [ 2 , 3 ]. Recently published studies have reported that polyphenols, especially anthocyanins [ 4 , 5 ], phenolic acids [ 6 ], and flavonols [ 7 ], as well as iridoids [ 8 ] and hydrolysable tannins [ 9 ] can prevent bone loss through different mechanisms. All these substances are present in cornelian cherries, in varying amounts, making their extracts promising candidates for antiosteoporotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that bone metabolism can be modulated by nutrients [ 2 , 3 ]. Recently published studies have reported that polyphenols, especially anthocyanins [ 4 , 5 ], phenolic acids [ 6 ], and flavonols [ 7 ], as well as iridoids [ 8 ] and hydrolysable tannins [ 9 ] can prevent bone loss through different mechanisms. All these substances are present in cornelian cherries, in varying amounts, making their extracts promising candidates for antiosteoporotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the anthocyanins profile of the huckleberries accessions 9JOA3679-2, 9JOA3678-1, and 9JOA3682-3 may be particularly beneficial in terms of potential nutrition and health outcomes. Peonidins have received less attention for health research ( Ren et al, 2021 ; Semmarath et al, 2022 ), but peonidins levels are only slightly higher than in blueberries, so the two other accessions are mostly different in terms of their cyanidins and malvidins levels.…”
Section: Resultsmentioning
confidence: 99%
“…Davidson’s plum containing cyanidin 3-glucoside (8 mg/kg/day) reduced obesity-induced degeneration of knee cartilage in rats with diet-induced metabolic syndrome [ 67 ]. In osteoporosis, bone regeneration may be stimulated by anthocyanins by stimulating bone formation and inhibiting bone resorption [ 245 ]; examples include peonidin 3-glucoside and cyanidin [ 246 ]. Anthocyanins may also alter bone remodelling in osteoporosis by epigenetic regulation of osteoblast differentiation and apoptosis, and bone mineralisation [ 247 ].…”
Section: Therapeutic Actions Of Anthocyanins In Chronic Diseasesmentioning
confidence: 99%
“…The hypothesis of a “gut–joint axis” has been proposed to connect the changes in the gut microbiota and osteoarthritis factors such as age, gender, metabolism, central nervous system and joint injury [ 246 , 248 ]. Decreasing serum lipopolysaccharides and inflammatory responses by chronic ampicillin and neomycin treatment of osteoarthritic mice changed the microbiota and improved the signs of osteoarthritis [ 249 ].…”
Section: Therapeutic Actions Of Anthocyanins In Chronic Diseasesmentioning
confidence: 99%